Deep Synoptic Array Science: A 50 Mpc Fast Radio Burst Constrains the Mass of the Milky Way Circumgalactic Medium - Ravi, Vikram; Catha, Morgan; Chen, Ge; Connor, Liam; Cordes, James M.; Faber, Jakob T.; Lamb, James W.; Hallinan, Gregg; Harnach, Charlie; Hellbourg, Greg; Hobbs, Rick; Hodge, David; et al. (The Astronomical journal, 2025)
We present the Deep Synoptic Array (DSA-110) discovery and interferometric localization of the so far nonrepeating FRB 20220319D. The FRB originates in a young, rapidly star-forming barred spiral galaxy, IRAS 02044+7048, at just 50 Mpc. Although the NE2001 and YMW16 models for the Galactic interstellar-medium (ISM) contribution to the DM of FRB 20220319D exceed its total observed DM, we show that uncertainties in these models accommodate an extragalactic origin for the burst. We derive a conservative upper limit on the DM contributed by the circumgalactic medium (CGM) of the Milky Way of 47.3 pc cm −3 , based on a pulsar nearby on the sky to FRB 20220319D that is used to estimate the ISM DM. This limit implies that the total Galactic CGM mass is <10 11 M ⊙ , and that the baryonic mass of the Milky Way is ≲60% of the cosmological average given the total halo mass. More stringent albeit less conservative constraints are possible when the DMs of pulsars in the distant globular cluster M53 are additionally considered. Although our constraints are sensitive to possible anisotropy in the CGM and to the assumed form of the radial-density profile, they are not subject to uncertainties in the chemical and thermal properties of the CGM. Our results strongly support scenarios commonly predicted by galaxy-formation simulations wherein feedback processes expel baryonic matter from the halos of galaxies such as the Milky Way.